Proto-professionalism: Opportunities for student learning and service to homeless people - Anderson, Elizabeth; Kinnair, Daniel; Ford, Jenny; Bleazard, Lucy; Malcherczyk, Steve (International Journal of Practice-based Learning in Health and Social Care, 2023)
The concepts of professionalism including ethical practice, reflection, self-awareness, respect, teamwork and social responsibility are present in the healthcare curriculum but rarely learned in combination. The concepts can be combined when students receive practical experiences on the challenges of delivering health and social care to populations experiencing poverty and disadvantage. We report on work with homeless people in our local communities designed to align social accountability responsibilities with healthcare curricula through a student volunteering project; initially established in a medical school. Using an ethical approach we developed this learning through a staff-student-community partnership. The outcome was learning consisting of theoretical teaching, practice learning and the potential to volunteer. We report on the development phases over several years (2013-2017). The pedagogical evaluation used a sequential mixed methods approach. One hundred and ninety-five student participants scored pre- and post-questionnaires. Of these 75% completed reflective assignments and many went on to volunteer. Twenty of those who volunteered participated in one-to-one interviews. Scored data were analysed statistically and reflective written materials were analysed using content analysis. The interview data were analysed using thematic analysis. The learning was positively experience and students reported changed attitudes and understandings of homelessness. Practice-placements and volunteering further enhanced these insights and student’s perceptions of readiness for clinical practice. This can be described as proto-professionalism. The student-staff-community partnership offers an ethical platform on which to build sustainable local outreach projects. The students gained a deeper appreciation of social injustice for homeless people.